Single dose pharmacokinetic study of lithium in Taiwanese/Chinese bipolar patients. - Lee CF; Yang YY; Hu OY (Australian & New Zealand Journal of Psychiatry, 1998)
OBJECTIVE: The purpose of this study is to investigate the single dose pharmacokinetics of lithium in Taiwanese/Chinese bipolar patients for future interracial comparisons. METHOD: Eight bipolar patients took 900 mg of lithium carbonate after overnight fasting. Blood samples of 5 mL were taken after 15 min, 30 min, 45 min, 1 h, 2 h, 3 h, 4 h, 7 h, 9 h, 15 h, 25 h and 31 h after dosing. The computer programs CSTRIP and PCNONLIN were used for pharmacokinetic analysis. RESULTS: The pharmacokinetic parameters obtained were as follows: Cmax, 0.970 +/- 0.170 (SD) mmol/L; Tmax, 1.59 +/- 0.78 h; AUC31 h = 548.9 +/- 135.4 mmol x m/L; AUC to infinity = 722.6 +/- 262.7 mmol x m/L; beta-half-life = 16.3 +/- 7.18 h; kappa-half-life = 0.613 +/- 0.442 h; Cl(oral) = 1.13 +/- 0.39 mL/min/kg; Vd/F = 1.43 +/- 0.387 L/kg. Most of the pharmacokinetic parameters were within the ranges reported in investigations of Caucasian subjects. CONCLUSIONS: This study showed that racial differences in lithium pharmacokinetics might not exist. We suggest that methodological designs, including method of blood sampling, measurement of lithium, and pharmacokinetic and statistical calculations, be standardised if future cross-ethnic comparisons are to be conducted.